DIMENSI KEILAHIAN SUNDA WIWITAN DALAM UPACARA SEREN TAUN DI CIGUGUR - Willfridus Demetrius Siga; Kurniasih . .; Alfonsus . Sutarno; Bartolomeus . Samho; Valerianus Beatae Jehanu (Jaqfi: Jurnal Aqidah dan Filsafat Islam, 2022)
Local religions in Indonesia are generally perceived as culture, not religion. The local religious tradition that existed before the world religion was seen as something with a profane dimension, not sacred. As a result, the divine dimension of local religion is denied. This ethnographic research aims to reveal the divinity dimension of local religion by taking a case study of the local religion of Sunda Wiwitan in Cigugur, Kuningan, West Java. The divine dimension of Sunda Wiwitan can be found in a special way in the entire series of Seren Taun ceremonies, namely the thanksgiving ceremony for the harvest as well as the Sunda Wiwitan religious holiday. In prayers, sacred places and times, ritual materials, music, songs and mantras, ceremonial clothing, performers, and sacred figures all manifest the existence of a supernatural figure (God). The dimension of divinity depicted in the local Sunda Wiwitan religion is very relevant and significant for developing an inclusive and appreciative attitude towards the diversity of religious traditions in Indonesia. With it, the promotion of peace and inter-religious harmony is also possible to construct.